Assessment of Measurement-Based Care to Improve Outcomes in Patients with Allergic Rhinitis in an Open-Label, Prospective Study (Canadian Allergy & Immunology Today, 2023)
Despite available treatments for allergic rhinitis (AR), patients are often dissatisfied with their treatment and experience uncontrolled symptoms. Measurement-based care is the systematic use of standardized measurements used during office visits to inform treatment decisions. The Improving Symptom Control of Allergic Rhinitis (ICAR) study determined if the assessment and management of AR through measurement-based care could improve patient outcomes. Methods ICAR was a real-world, open-label, prospective, multicenter study conducted in Canada between September 2021 and December 2021. Enrolled adult patients (n=503) with AR were categorized as treatment-naïve, uncontrolled despite AR treatment, or requiring a treatment switch due to adverse effects. AR symptoms and symptom control were assessed by the patient using the Rhinitis Control Assessment Test (RCAT) and, by both the patient and the clinician, on a visual analog scale (VAS) at baseline and after 4 weeks of 10 mg daily oral rupatadine.